Puerto Rican pre-teenagers’ physical and sedentary activities, dietary trends, and stress (Research, Society and Development, 2023)
The purpose of this study was to identify and analyze physical activity, sedentary activity, and dietary behaviors of preadolescents in Puerto Rico. A secondary purpose was to examine perceived stress and the weight status of the Puerto Rican preadolescents. Participants were 107 pre-teenagers (ages 6 to 11 years old) attending public elementary schools in Puerto Rico. Using a descriptive cross-sectional survey study design, we collected data on participants’ physical activity, sedentary activity, dietary behaviors, and perceived stress. We also measured participants’ height and weight, and calculated body mass indices. MINITAB descriptive and inferential statistical tests were used in analyzing the data. Results indicate that, on average, the participants partook in physical activities for less than 10 minutes each day, but regularly participated in sedentary activities. Their food behaviors varied. ANOVA tests revealed they were not significantly different in height and weight as a function of gender (F = 0.78, p = .46), but differed significantly in height and weight as a function of age (F = 7.02, p < .00) with older children, on average at greater height and weight. On average, the participants’ BMI scores fell within the healthy category, but ranged from healthy to overweight. Mostly, the participants had low levels of stress, worry, or nervousness. Instead, they felt supported and loved. In conclusion, more research in kinesiology is needed, whereby investigators explore, interrogate, and analyze health and social inequities associated with physical and sedentary activities, stress events, and food behaviors of preadolescents in Puerto Rico.